2019
DOI: 10.1186/s13046-019-1426-2
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy of brain metastases: breaking a “dogma”

Abstract: Until very few years ago, the oncology community dogmatically excluded any clinical potential for immunotherapy in controlling brain metastases. Therefore, despite the significant therapeutic efficacy of monoclonal antibodies to immune check-point(s) across a wide range of tumor types, patients with brain disease were invariably excluded from clinical trials with these agents. Recent insights on the immune landscape of the central nervous system, as well as of the brain tumor microenvironment, are shedding lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
82
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 92 publications
0
82
0
3
Order By: Relevance
“…We cannot exclude the potential efficacy of ICIs administrated as single agent in patients with brain metastases at present, and the superiority of combination therapy should be validated in larger trials. Currently, several ongoing trials have been investigating the efficacy and safety of ICIs combined with other treatment options in treating patients with brain metastases, such as chemotherapy and radiotherapy (52). We can expect more rigorous evidence for the choice of treatment regimens in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We cannot exclude the potential efficacy of ICIs administrated as single agent in patients with brain metastases at present, and the superiority of combination therapy should be validated in larger trials. Currently, several ongoing trials have been investigating the efficacy and safety of ICIs combined with other treatment options in treating patients with brain metastases, such as chemotherapy and radiotherapy (52). We can expect more rigorous evidence for the choice of treatment regimens in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there may be a selection bias to some extent. Up to date, several clinical trials are ongoing investigating ICIs in solid tumor with brain metastases (52). Further investigations are warranted to elucidate organ-specific tumor immune microenvironment, and more randomized trials are required to compare the efficacy of immunotherapy with conventional therapy based on metastatic sites.…”
Section: Discussionmentioning
confidence: 99%
“…A summary of the studies considered is detailed in Table 1 ; a summary of covariate distributions is shown in Supplementary Figure 1 . The tumor types tested included brain metastases originating from melanoma ( N = 33), NSCLC ( N = 2), and pooled solid tumors (mainly melanoma and NSCLC, N = 5), which can be explained by the broad use of ICI drugs in the treatment of advanced melanoma and NSCLC combined with a high rate of brain metastases observed in these indications ( 62 ). Stereotactic RT regimens only were used in 29 studies; in the remaining 11 studies, conventional RT regimens were also considered.…”
Section: Resultsmentioning
confidence: 99%
“…Brain metastases represent an unmet medical need in current oncologic care. Given the poor prognosis of patients with brain metastases, particularly in lung adenocarcinoma patients, there is critical need to improve our understanding of the mechanisms underlying the pathogenesis as well as to identify novel targets for immune therapies [53][54][55] . Advances in singlecell RNA sequencing (scRNA-seq) have allowed for a comprehensive analysis of intra-tumoral heterogeneity and tumor immune microenvironment in various cancer types at primary sites 38,39,43,49,[56][57][58] .…”
Section: Discussionmentioning
confidence: 99%